2012
DOI: 10.1186/1556-276x-7-54
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties of PZT/BFO multilayer thin films prepared using the sol-gel method

Abstract: In this study, Pb(Zr0.52Ti0.48)O3/BiFeO3 [PZT/BFO] multilayer thin films were fabricated using the spin-coating method on a Pt(200 nm)/Ti(10 nm)/SiO2(100 nm)/p-Si(100) substrate alternately using BFO and PZT metal alkoxide solutions. The coating-and-heating procedure was repeated several times to form the multilayer thin films. All PZT/BFO multilayer thin films show a void-free, uniform grain structure without the presence of rosette structures. The relative dielectric constant and dielectric loss of the six-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 9 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…The leakage current density measured was almost two orders of magnitude less in BLFTO. 14 Based on the previous studies, pure BFO showed a leakage current density of $10 À2 A/cm 2 (at 1 V), 25 which is one order higher as compared to the observed value of $10 À3 A/ cm 2 (at 1 V) in our BLFTO film. The dark J-V curve of the BLFTO cell shows a high resistance state, irrespective of the voltage.…”
Section: A)mentioning
confidence: 52%
“…The leakage current density measured was almost two orders of magnitude less in BLFTO. 14 Based on the previous studies, pure BFO showed a leakage current density of $10 À2 A/cm 2 (at 1 V), 25 which is one order higher as compared to the observed value of $10 À3 A/ cm 2 (at 1 V) in our BLFTO film. The dark J-V curve of the BLFTO cell shows a high resistance state, irrespective of the voltage.…”
Section: A)mentioning
confidence: 52%
“…60,61,70, BFO-based multilayer structures have been shown to promote the desired electrical properties and/or new physical phenomena, 60,61,70,71,77,110, such as a larger remnant polarization, improved magnetoelectric coupling, and photovoltaic behavior. 61,70,[366][367][368][369][370][371][372][373][374][375][376][377][378][379][380][381][382][383][384]772,848,849 Although some of the properties of BFO thin films can be improved by forming the heterostructure, the P r value is often limited to below 60 μC/cm 2 60,70,366-375,377-379,381,383,384 due to the additive layers having lower or even zero P r values. There have been surprisingly large P r values reported for the heterostructure films consisting of BFO and non-ferroelectric layers.…”
Section: Multilayer Structurementioning
confidence: 99%
“…Secondly, the BiFeO 3 bulk material exists the large leakage current since the existence of the mixed valence Fe 2+ /Fe 3+ ions and oxygen vacanvies [11,12]. Thirdly, the BiFeO 3 shows very weak even no ferromagnetism from a near-linear magnetization-magnetic field (M-H) relation [13].…”
mentioning
confidence: 99%